2011
DOI: 10.1039/c1an15302a
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive kernel independent component analysis and UV spectrometry applied to characterize the procedure for processing prepared rhubarb roots

Abstract: By determination of the number of absorptive chemical components (ACCs) in mixtures using median absolute deviation (MAD) analysis and extraction of spectral profiles of ACCs using kernel independent component analysis (KICA), an adaptive KICA (AKICA) algorithm was proposed. The proposed AKICA algorithm was used to characterize the procedure for processing prepared rhubarb roots by resolution of the measured mixed raw UV spectra of the rhubarb samples that were collected at different steaming intervals. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It should be noted that the estimated DCs may be the mirrors of the real sources that likes using InfomaxICA, FastICA, and kernel ICA, in which there is no nonnegative constraint to the mixing matrix [4][5][6]. On these cases, the estimated DCs should be mirrored according to the chemical information of the spectra of the components represented or use other ICA algorithms to cross verify the estimated sources.…”
Section: Estimation Of Source Spectral Profiles From Synthetic Mixed ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the estimated DCs may be the mirrors of the real sources that likes using InfomaxICA, FastICA, and kernel ICA, in which there is no nonnegative constraint to the mixing matrix [4][5][6]. On these cases, the estimated DCs should be mirrored according to the chemical information of the spectra of the components represented or use other ICA algorithms to cross verify the estimated sources.…”
Section: Estimation Of Source Spectral Profiles From Synthetic Mixed ...mentioning
confidence: 99%
“…Recent years, we used independent component analysis (ICA) to directly estimate source spectral profiles, which ere considered as the independent components (ICs), from the mixed spectra that were measured during Chinese medical plants processing batches [4][5][6]. By inspection of the peak features and variations of the relative concentrations of the extracted ICs, the main active components can be accounted and the endpoint of the processing batch can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelet kernel function, by virtue of the multi-scale nature of the wavelet transform and by providing an approximate orthogonal basis, combined with the ICA algorithm to analyze the data step-by-step, can improve the ability of the non-linear mapping and hence the data separation performance [21,22]. Although the above methods can handle non-Gaussian and complex non-linear data and improve the data-processing accuracy, they mainly emphasize the ability to interpret the independent variables themselves and ignore the ability to interpret the dependent variables [23,24]. It is often applied to fault detection and the data processing of industrial processes and is unable to perform regression analysis and build quality prediction models for the dependent variable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, processing is important to moderate reactions (such as anaphylaxis and allergies), diminish adverse events and modify detrimental properties (such as disagreeable flavors and odors) [ 6 ]. Experimental studies have been conducted to confirm the benefits of processing medicinal herbs to reduce their toxicity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al compared the levels of anthraquinones and tannins in several processed RR extracts using different methods and found RR steaming decreased combined anthraquinones, while there was little change in total anthraquinones and tannins. Additionally, water-steamed RR decreased the anthraquinone glycoside content [ 7 , 8 ]. Doui et al reported that alcohol-soaking in 16 % ethanol and then steaming of RR decreased the sennoside content, while the processing increased the anthraquinone content [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%